2014
DOI: 10.1016/j.jtcvs.2013.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of left ventricular load by a continuous-flow left ventricular assist device with a native heart load control system in a chronic heart failure model

Abstract: The system offers the possibility to control the left ventricular load by changing the rotational speed of a continuous-flow assist device in synchronization with the cardiac cycle. This system should provide the most favorable left ventricular loading conditions for recovery of the native heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…We developed a rotational speed (RS) modulation system for EVAHEART that can change the RS in synchronization with the cardiac cycle of the native heart. We have previously reported that this system can change the native heart load, alter arterial pulsatility, enhance myocardial perfusion, and may be able to prevent aortic insufficiency without harmful effects on hemolysis . Although these properties can be beneficial to patients under CF‐LVAD, there remains a concern that the repeated acceleration and deceleration of an impeller may affect vWF dynamics.…”
mentioning
confidence: 99%
“…We developed a rotational speed (RS) modulation system for EVAHEART that can change the RS in synchronization with the cardiac cycle of the native heart. We have previously reported that this system can change the native heart load, alter arterial pulsatility, enhance myocardial perfusion, and may be able to prevent aortic insufficiency without harmful effects on hemolysis . Although these properties can be beneficial to patients under CF‐LVAD, there remains a concern that the repeated acceleration and deceleration of an impeller may affect vWF dynamics.…”
mentioning
confidence: 99%
“…Increasing the size of the system by adding a flow meter is also undesirable for portable extracorporeal RBPs. Furthermore, there is a need to measure the flow rate and the pressure in VADs for novel therapies that promote heart recovery, in which the flow rate of the VAD is controlled and the load to the biological heart deliberately increased .…”
mentioning
confidence: 99%
“…Our RS modulation control system can alter the native heart load , pulsatility , and blood flow of the coronary artery by changing the RS in the systolic and diastolic phases. Based on our previous protocol, the variance in the RS between systole and diastole was set at 500 rpm . Umeki et al used our RS modulation system in an acute ischemic heart model, and achieved a smaller LVEDV in the counter‐pulse mode and desirable LVEDV control.…”
Section: Discussionmentioning
confidence: 99%